STUDI SIFAT FISIK DAN SIFAT MEKANIK KOMPOSIT EPOKSI-ALUMINA - , RUSNOTO,S.T ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Composites material can be defined as a combination of two or more materials that differ in form and chemical composition and which are essentially insolube each other. This research aims to investigate the influence of alumina powder on tensile strength, bending strength, fracture thoughness, abrasiveness, density and impac strength of epoxy/alumina composites. Materials used in this research were epoxy as a matrix and alumina as a filler. Epoxy (with a code of DGEBA DER 331) was purchased from DOW Chemical England. Alumina was obtained from Merck K Ga A Darmstadt Germany. Hardener (with a type of 2,4,6 Tris-Dymethilaminomethyl) phenol was purchased from Sigma Aldrich England. Prior to use, the alumina powder was heated up at 80° C for 2 hours. Composites were produced with various amount of alumina powder of 0, 10, 20 and 30 wt %. Each composition of epoxy and alumina powder was mixed and stired mechanically with 800 rpm at 80°C for 1 hour. During stirring, the hardener was added. The mixture was then placed in a vacum chamber for 1 minutes to remove air bubble, and followed by pouring the mixture into a metal mould. The examples were cured at 80°C for 1 hour. Post curing of the composites was performed in a oven at 120°C for 2 hour. The specimens were carried act several mechanical testing such as tensile, three-point bending, fracture toughness, abrasiveness, density and impact test. The microstructures and fracture surfaces were observed using optical microscope and scanning electron microscope (SEM). The results of the research show the addition of alumina has no significant effect on the tensile and bending strength. Epoxy-alumina composits with 20 wt% of alumina showed highest values in flexural modulus, fracture toughness, abrasiveness, impac strength i.e., 4316,1 Mpa, 2 MPa.m1/2, 1,1x10-6 mm2/kg, 4177J/mm2, respectively.